2012
DOI: 10.1155/2012/574025
|View full text |Cite
|
Sign up to set email alerts
|

Active Roles of Tumor Stroma in Breast Cancer Metastasis

Abstract: Metastasis is the major cause of death for breast cancer patients. Tumors are heterogenous cellular entities composed of cancer cells and cells of the microenvironment in which they reside. A reciprocal dynamic interaction occurs between the tumor cells and their surrounding stroma under physiological and pathological conditions. This tumor-host communication interface mediates the escape of tumor cells at the primary site, survival of circulating cancer cells in the vasculature, and growth of metastatic cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
63
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 95 publications
(125 reference statements)
0
63
0
Order By: Relevance
“…Emerging research is illuminating the underlying cellular and molecular events controlling the metastatic cascade from onset to colonization. Now it is defined that a reciprocal interplay between tumor cells, stromal cells and the ECM mediate metastasis in epithelial cancers (Khamis et al, 2012). The essential components of metastatic niches include ECM proteins, secreted enzymes, growth factors, cytokines and other molecules that carry information to cancer cells.…”
Section: Metastatic Nichesmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging research is illuminating the underlying cellular and molecular events controlling the metastatic cascade from onset to colonization. Now it is defined that a reciprocal interplay between tumor cells, stromal cells and the ECM mediate metastasis in epithelial cancers (Khamis et al, 2012). The essential components of metastatic niches include ECM proteins, secreted enzymes, growth factors, cytokines and other molecules that carry information to cancer cells.…”
Section: Metastatic Nichesmentioning
confidence: 99%
“…Further, the stromal compartment contains various bone-marrow-derived cells (BMDCs) such as macrophages, mast cells, neutrophils, and lymphocytes recruited by the primary tumor cells to increase tumor cell migration, angiogenesis, and invasion. Observation of immune infiltrates at sites of focal disruptions of the myoepithelial cell layer in breast tissues suggests a potential role of these cells in tumor malignancy and metastatic spread (Khamis et al, 2012; Kuznetsov et al, 2012). Collective dissemination is a frequent mechanism for metastatic spread and whether the most invasive, keratin 14+ (K14+) expression in breast cancer cells regulate cell–cell adhesion, cell–matrix adhesion, and immune evasion (Cheung et al, 2013; Cheung et al, 2016).…”
Section: Metastatic Nichesmentioning
confidence: 99%
“…Metastasis is the primary cause of breast cancer-related deaths; however, the molecular mechanisms underlying this process are still poorly understood. It has been well established that the tumor microenvironment plays an important role in breast cancer metastasis (3)(4)(5)(6). Tumor-associated macrophages (TAMs) make up the largest population of stromal cells that suppress antitumor immunity and foster tumor progression in mouse models of breast cancer (3,(6)(7)(8).…”
mentioning
confidence: 99%
“…Some studies reported cytoplasmic positivity for ALDH1 expression in tumor cells only [6,11,12], and some studies detected both cytoplasmic positivity of tumor cells and stromal positivity for ALDH1 expression [15,24,25]. Since tumor stromal cells are known to be involved in tumor growth and metastasis [21,33], differences in the distribution and characteristics of cytoplasmic cellular or stromal expression of ALDH1 need to be elucidated to better understand the exact role of ALDH1 expression in breast cancer. A few previous reports have analyzed the implications of cellular and stromal expression.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor stromal cells are a part of the local microenvironment, which includes myoepithelial cells, fibroblasts, myofibroblasts, endothelial cells, and inflammatory cells. The tumor stroma is known to play a role in breast cancer metastasis [21]. However, few studies have evaluated the prognostic value and related characteristics of both tumor cell and stromal expression.…”
mentioning
confidence: 99%